2008
DOI: 10.1016/j.npep.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of GalR2 knockout mice in anxiety- and depression-related behavioral tests

Abstract: Neuropeptide galanin modulates a variety of central nervous system functions by signaling through three G-protein-coupled receptor subtypes, GalR1 through GalR3. Galanin and its receptors are expressed at high levels in the limbic structures of the rodent brain. Intracerebroventricular injection of galanin has been shown to modulate depression and anxiety-like behaviors in the rat. We have previously shown that chronic antidepressant treatments increase the binding of a GalR2-preferring ligand, galanin (2-11),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 52 publications
2
47
0
1
Order By: Relevance
“…Consistent with an antidepressant-like effect of GAL 2 receptor signaling (14), Lu et al (15) observed a depressive-like phenotype in GAL 2 receptor-deficient (GAL 2 -KO) mice but found no GAL 2 receptor-mediated effects on anxiety-related behavior. GAL 3 receptor stimulation was suggested to induce a depression-like profile because decreased immobility and increased swimming in the rat FST were observed after treatment with the nonpeptidergic GAL 3 receptor-selective antagonist 1-phenyl-3-[[3-(trifluoromethyl)phenyl]imino]-1H-indol-2-one (SNAP 37889).…”
Section: Significancementioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with an antidepressant-like effect of GAL 2 receptor signaling (14), Lu et al (15) observed a depressive-like phenotype in GAL 2 receptor-deficient (GAL 2 -KO) mice but found no GAL 2 receptor-mediated effects on anxiety-related behavior. GAL 3 receptor stimulation was suggested to induce a depression-like profile because decreased immobility and increased swimming in the rat FST were observed after treatment with the nonpeptidergic GAL 3 receptor-selective antagonist 1-phenyl-3-[[3-(trifluoromethyl)phenyl]imino]-1H-indol-2-one (SNAP 37889).…”
Section: Significancementioning
confidence: 73%
“…These contradictory results may be attributed to the differential actions of the three GAL receptor subtypes (34). Whereas stimulation of the GAL 2 receptor seems to be responsible for antidepressant-like effects (15,39,40), the inhibitory receptor subtypes GAL 1 (41) and GAL 3 seem to contribute to the prodepressive effects of GAL (42). Thus, in addition to its anxiolytic effect, the GAL 3 receptor antagonist SNAP 37889 exerts an antidepressant-like activity in rats (16).…”
Section: Discussionmentioning
confidence: 99%
“…Galanin has been linked to the regulation of metabolic and osmotic homeostasis (Crawley, 1999;Landry et al, 2000;Gundlach, 2002), reproduction (Rossmanith et al, 1996;Gundlach, 2002), nociception (Liu and Hökfelt, 2002), arousal/sleep (Sherin et al, 1998;Steininger et al, 2001), and cognition (McDonald et al, 1998;Kinney et al, 2002), and these functions have been subsequently linked to the actions of specific galanin receptors. For example, GAL 1 has been linked strongly with the CNS and PNS and with modulatory actions on neurotransmission and anxiety, reward, and nociception (see details below), whereas GAL 2 is more broadly expressed and in the CNS is implicated in neurodevelopment (Burazin et al, 2000), modulation of both neurotransmission and affective behaviors (Karlsson and Holmes, 2006;Lu et al, 2008), neurite outgrowth in normal hippocampus (Elliott-Hunt et al, 2004), and neuronal survival and neurogenesis in injured hippocampus (Elliott-Hunt et al, 2004;Mazarati et al, 2004;Pirondi et al, 2005a) (see details below). Galanin and galanin receptors have more recently been associated with neurogenesis and embryonic and adult neural stem cells (see section VIII).…”
Section: Neuronal Actions Of Galanin In the Central And Peripheralmentioning
confidence: 99%
“…Despite their development by two laboratories (Gottsch et al, 2005;Hobson et al, 2006;Lu et al, 2008), the profile of GAL 2 -KO mice in terms of seizures and epilepsy has not be reported. In contrast, overexpression of galanin in seizure pathways, using both transgenic and virus vector transfection methods, retards the epileptic process.…”
Section: E Physiologic and Pharmacologic Actions Of Galanin In The Dmentioning
confidence: 99%
“…Los investigadores relacionan los efectos positivos inducidos por el ejercicio con el incremento de la galanina. Este es un neuropéptido que tiene efectos antidepresivos y anticonvulsivantes (79)(80)(81)(82)(83).…”
Section: ¿Cómo Se Explica La Mejoría De La Comorbilidad Depresiva En unclassified